PERANAN SYEKH MUSTAFA AL-KHALIDIYAH BIN MAHRUM MOHAMMAD BAQIR DALAM MENYEBARKAN AGAMA ISLAM DI KECAMATAN PELALAWAN (1862-1880) - Aisyah Nur Hanifah; Isjoni Isjoni; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The Islamic History of Riau is a form of past reality towards the whole fact that has been inherited by the publishers of Islam. The process of entering Islam into Riau, brought by traders from Arabia, Persia, and Hedramaut who have the purpose to trade while broadcasting the teachings of Islam. Based on the results of research from Azra said, there had been a relationship between the population of Riau and the Arabs which was estimated to have occurred in the third century BC. In addition, the role of ulama has a major influence in spreading Islam. Religious broadcasters are figures who have contributed to bringing Islamic reform in Indonesia through the path of preaching delivered in a peaceful and friendly manner. Islam entered Pelalawan Subdistrict, originating from the Lima area of Kampar City. The route includes: Bangkinang-Kuok-Salo-Rumbio and Air Tiris which is located on the banks of the Kampar Kanan river until finally it comes to Pelalawan District, precisely in Sengkulim Village. Sheikh Mustafa Al-Khalidiyah bin Mahrum Mohammad Baqir was a scholar who contributed to spread Islam thoroughly to the people of Pelalawan in 1862 AD The role given by Sheikh Mustafa Al - Khalidiyah bin Mahrum Mohammad Baqir in spreading Islam among them, succeeded in building Surau and The mosque, making drum, making a book on the journey of da'wah and genealogy, and the last party succeeded in Islamizing the Pelalawan community with the teachings of the Naqsabandiyah Tariqat which grew up in Pelalawan to this day.Key Words : The Role Of Syeikh Mustafa Al – Khalidiyah Bin Mahrum Mohammad Baqir, Spreading Islam Region In Pelalawan Regency